DIPLOMASI PUBLIK TIONGKOK KE AMERIKA SERIKAT PADA ERA HU JINTAO - Tri Fauzi Tadif; Inda Mustika Permata; Anita Afriani Sinulingga (Frequency of International Relations (FETRIAN), 2020)
This research discusses China's efforts to eliminate China Threat's perception in the United States on Hu Jintao reign. The Gallup survey indicator shows that the people of the United States began to view China as a threat related to the rise of China. To eliminate this assumption, during the reign of Hu Jintao, China began to carry out public diplomacy efforts to the United States in order to improve its image. The purpose of this study is to explain China's public diplomacy efforts to the United States during Hu Jintao's time as an effort to improve the image. This research was discussed using the concept of R.S Zaharna's public diplomacy.This research uses qualitative methods with library research data collection techniques. China's public diplomacy is mostly carried out by state actors with a cultural approach that targets the community, institutions and community. This study saw that almost all public diplomacy efforts such as student exchanges, cultural institution development and the establishment of sister cities by China had a positive impact, marked by China's favorable index in the United States which rose 40% in 2012.